2003
DOI: 10.1021/ma021045i
|View full text |Cite
|
Sign up to set email alerts
|

Importance of π-Stacking in Photoreactivity of Aryl Benzobisoxazole and Aryl Benzobisthiazole Compounds

Abstract: Aryl benzobisoxazole and aryl benzobisthiazole compounds in the solid state and in solution have completely different photoreactivity. In the solid state, intermolecular π-stacking interactions between these molecules lead to excimer formation. The excimer undergoes a photoinduced electron transfer to generate an ion radical pair. In the presence of oxygen, the anion radical transfers an electron to molecular oxygen to form superoxide. The cation radical undergoes bond cleavage followed by hydrogen abstraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…PBO and PBZT, from here on represented as PBX, have a unique extended rigid‐rod‐like configuration and are called rigid‐rod polymers 16. Photophysics and photochemistry of PBX have been reported by workers at The Dow Chemical Company, and they also proposed a PET mechanism for PBX photo‐oxidation 12, 13. This article compares the similarities and differences of PPO and PBX under photo‐oxidative conditions.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…PBO and PBZT, from here on represented as PBX, have a unique extended rigid‐rod‐like configuration and are called rigid‐rod polymers 16. Photophysics and photochemistry of PBX have been reported by workers at The Dow Chemical Company, and they also proposed a PET mechanism for PBX photo‐oxidation 12, 13. This article compares the similarities and differences of PPO and PBX under photo‐oxidative conditions.…”
Section: Introductionmentioning
confidence: 81%
“…PET is a key step in biological systems, organic reactions, organometallic and inorganic chemistry, catalysis and molecular‐level electronics 8, 9. Poly(2,4‐dimethyl‐1,4‐phenylene oxide) (PPO),10, 11 poly(benzo[1,2‐ d :5,4‐ d ′]bisoxazole‐2,6‐diyl‐1,4‐phenylene) (PBO) and poly (benzo[1,2‐ d :4,5‐ d ′]bisthiazole‐2,6‐diyl‐1,4‐phenylene) (PBZT)12, 13 (Scheme ) have been reported to undergo self‐sensitized PET. In this mechanism, an excited polymer repeating unit undergoes electron transfer with another unit to generate a radical‐cation and radical‐anion pair.…”
Section: Introductionmentioning
confidence: 99%
“…The compounds in solution are stable even after prolonged irradiation, suggesting that intermolecular π-stacking plays a very important role in photoreactivity for these molecules. Reversible redox reagents, such as ferrocene compounds, are found to retard the subsequent reactions from the photoinduced electron-transfer reaction and hence improve the PBO photostability (353).…”
Section: Compressive Properties As Listed Inmentioning
confidence: 99%
“…Some studies of the degradation of PBO fibers have been reported, including thermal degradation, hydrolysis, and photodegradation 9–15. Walsh et al found that exposure to moisture results in loosening of the PBO fiber morphology, leading to an increase in the number and size of defects 10.…”
Section: Introductionmentioning
confidence: 99%
“…UV–Vis radiation primarily hydrolyzes the material near the fiber surface with the attendant formation of amide linkages. So et al found that aryl benzobisoxazole and aryl benzobisthiazole compounds both in the solid state and in solution have completely different photoreactivities 11. In the solid state, excimers form and undergo photo‐induced electron transfers to generate an ion radical pair.…”
Section: Introductionmentioning
confidence: 99%